How does regulating doctors' admissions affect health expenditures? Evidence from Switzerland - Michel Fuino; Philipp Trein; Joël Wagner (BMC, 2022)
Abstract Background Cost containment is a major issue for health policy, in many countries. Policymakers have used various measures to deal with this problem. In Switzerland, the national parliament and subnational (cantonal) governments have used moratoriums to limit the admission of specialist doctors and general practitioners. Methods We analyze the impact of these regulations on the number of doctors billing in free practice and on the health costs created by medical practice based on records from the data pool of Swiss health insurers (SASIS) from 2007 to 2018 using interrupted time series and difference-in-differences models. Results We demonstrate that the removal of the national moratorium in 2012 increased the number of doctors, but did not augment significantly the direct health costs produced by independent doctors. Furthermore, the reintroduction of regulations at the cantonal level in 2013 and 2014 decreased the number of doctors billing in free practice but, again, did not affect direct health costs. Conclusions Our findings suggest that regulating healthcare supply through a moratorium on doctors' admissions does not directly contribute to limiting the increase in health expenditures.